Analysis of the domestic market of 1,2,4-triazole-containing drugs - M. V. Ohloblina; I. V. Bushuieva; V. V. Parchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
The modern market of medicines in Ukraine has the dynamics of constant development. At the same time, the dynamics of the pharmaceutical market depend entirely on the welfare of the population. Current features of quarantine restrictions have caused a number of distortions in drug consumption. Thus, after the introduction of quarantine in March 2020, part of the population panicked, which forced them to stockpile vital goods. At this time, there was a significant increase in sales of drugs, including antiviral, antiseptic, and disinfectant activity. The dynamics of drug balances on the shelves reached +50 %. However, there was a sharp decline in consumption between June-October 2020 and April 2021 due to the full effect of quarantine restrictions and March-April 2022 due to martial law in Ukraine. Today, the rate of purchases and balances of medicines on the shelves of pharmacies exceeds the rate of growth of their sales.